2017
DOI: 10.1007/s00198-017-4112-2
|View full text |Cite
|
Sign up to set email alerts
|

Atypical subtrochanteric fractures in Korean hip fracture study

Abstract: In Korean, ASF were rare. Higher BMI and use of bisphosphonate were significant risk factors of ASF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…However, our study also found that nearly half of AFF in our population were in patients not exposed to bisphosphonates, 47.8% of patients with AFF had no previously documented exposure to BP. This was similar to a previous Korean study who found 64.7% of their cohort with no previous BP exposure 19 and past case series from Singapore 20 , in contrast studies in the ethnic white population have shown that majority of AFF occurs in the context of BP exposure 21 . It is also interesting to…”
Section: Discussionsupporting
confidence: 91%
“…However, our study also found that nearly half of AFF in our population were in patients not exposed to bisphosphonates, 47.8% of patients with AFF had no previously documented exposure to BP. This was similar to a previous Korean study who found 64.7% of their cohort with no previous BP exposure 19 and past case series from Singapore 20 , in contrast studies in the ethnic white population have shown that majority of AFF occurs in the context of BP exposure 21 . It is also interesting to…”
Section: Discussionsupporting
confidence: 91%
“…It is difficult to set up an adequately powered study because of the low incidence of AFF and healing of AFF can be affected by variables such as lower limb geometry (greater curvature of the femoral diaphysis) and location of fracture (subtrochanteric or diaphysis). [64][65][66] Above all, these results should be implied that TPTD works best when the fracture site is stable, either inherently or with surgical fixation. [67,68] The European Calcified Tissue Society suggested the use of TPTD after surgery of AFFs, even though strong evidence for improved fracture union is lacking.…”
Section: Does Tptd Aid the Union Of Aff?mentioning
confidence: 85%
“…[22] From multicenter prospective study revealed that higher BMI and use of bisphosphonate were significant risk factors of AFF. [23] The development of atypical fractures is not associated with osteoporosis but pathophysiology of stress fracture due to altered bone structure and biomechanics. [24] It has been proposed that patients with longterm use of bisphosphonate may have a low bone turnover condition with impaired new bone formation and our patients with AFF are also mostly treated with anti-resorptive (93.9%, 46 of 49).…”
Section: Discussionmentioning
confidence: 99%